KEMAMPUAN PENGGUNAAN JOSHI O MAHASISWA PROGAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI PADANG - Chandra Vitri Yantika; Refnaldi Refnaldi; Yulia Nova (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
This research is motivated by difficulties of students in using joshi o in sentences. This study aims to determine the ability of students to use joshi o as a marker of objects and places in sentences. The Method of this research is quantitative with descriptive method. The population of this study is the college student class of 2018 Japanese Language Education Studies Program State University of Padang is 64 students and the sample is 32 students with using simple random sampling method. This research data is taken by using objective test instrument. The result of the research indicate that the ability of students to use joshi o can be classified as a excellent with an average value of 71,1. The ability identifies joshi o as a marker and places in the classification more than enough with average value of 59,2. The findings also show that the ability to determine words before joshi o as a marker and place in the classification with praise with an average value of 83,1.